Coulomb Stress Change of the 2006 Pangandaran Earthquake (Mw 7.7) and Its Implication for Future Seismicity in the Sunda Subduction Zone - Hana Situmorang; Kayla Alexandra; Yudha Styawan; Rizki Wulandari (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2026)
The Pangandaran earthquake on July 17, 2006, with a magnitude of Mw 7.7, was a tsunami earthquake that triggered a massive tsunami along the southern coast of Java, causing extensive damage and claiming many lives. This study aims to analyze the distribution of Coulomb stress change (ΔCFF) resulting from the 2006 Pangandaran earthquake based on Nodal Plane 1 (NP1), Nodal Plane 2 (NP2), and a finite fault model as validation references. ΔCFF modeling was performed using a rectangular fault plane approach, with interpolation conducted at depths ranging from 0 to 40 km in 10-km intervals to identify the depth yielding the most representative stress distribution. Analysis results indicate that NP1 with strike 284°, dip 9°, and rake 87° at a depth of 10 km produces a ΔCFF distribution pattern most consistent with and representative of the aftershock distribution and closest to the finite fault model pattern. The stress loading zone (ΔCFF > 0) extends northward from the epicenter toward the southern coast of Java, indicating an increased potential for aftershocks in that segment. Meanwhile, the stress-shadow zone (ΔCFF < 0) in the central to western regions reflects the location of the main slip release. The shallow geometry of the NP1 fault plane (dip 9°) contributes to the extensive stress loading zone, reflecting the characteristics of the Sunda subduction megathrust interface. The results of this study indicate that the 2006 Pangandaran earthquake significantly transferred stress to the western and eastern segments of the subduction zone, implying a potential hazard of subsequent seismic activity in the southern Java region.